PLANNING AND DEVELOPMENT OF FRIED MEATBALL CHIPS PACKAGING PRODUCTS AT IRT AMNPQ WITH CONSUMERS' VOICES IN MIND - putri, made Savitri Purnamasari Yudana; Noor, Asep Mohamad (Sustainable Environmental and Optimizing Industry Journal, 2024)
The fried meatball chips industry has experienced significant growth in recent years, driven by consumer demand for convenient and tasty snack options. Packaging for these products often lacks innovation, leading to issues such as poor product protection, limited shelf life, and lack of brand differentiation. This study aims to develop an improved packaging solution for fried meatball chips that addresses these challenges while taking into account sustainability and consumer preferences. The study used a mixed methods approach, combining quantitative and qualitative techniques. Initially, a comprehensive market analysis was conducted to understand consumer behavior, packaging trends, and industry best practices. The final packaging solution was tested for its effectiveness in terms of product protection, shelf life extension, and consumer appeal through various laboratory and field tests. In addition, a life cycle assessment (LCA) was conducted to evaluate the environmental impact of the proposed packaging solution and identify opportunities for further improvement. The findings of this study contribute to the existing body of knowledge in the field of packaging design and development, specifically for the fried meatball chips industry. The proposed packaging solution offers improved product protection, shelf life extension, increased brand recognition, and improved sustainability, ultimately benefiting both producers and consumers.